A comprehensive study on public awareness about electronic medical records - SHREE, MS. K. C. RAJA; FATHIMA S, SHAMEEM (The journal of contemporary issues in business and government, 2020)
Electronic Medical Record (EMR) framework is a longitudinal electronic record comprising all patient data. It allows patient data information to keep an advanced clinical report. In others viewpoint, should be a digitalised variant to hospitalised persons clinical report should documented in manual outline.EMRs are something beyond a substitution for paper records. They adequately permit correspondence and coordination among individuals from a medical care group for ideal patient consideration. Digital medical record exploits medical assist regarded a record registered report diverse extensive stretches. An EMR is standard online medical data used by physicians and other healthcare professionals for examination and treatment of patient issues. The frameworks coordinate accurate documentation involved to implement changes in setting appointing, charging, check out. EMR became an important innovation and a tool for record keeping and transferring medical records. Improve quality, security, effectiveness, and decrease health variations. Maintain privacy and confidentiality of patient well-being data. Although patient clinical records are more available and accessible than ever before, processing system upgrades are continually enhancing medical data information workflow and physician-patient interactions.